Comparison of Tramadol with Combination of Tramadol and Ketorolac for Post Cesarean Section Analgesia - Regmi, Nabin Kumar; Jahan, Kamar; Rai, Purnima; Bhandari, Ankur (Journal of Nepalgunj Medical College, 2020)
Introduction: Effective post-operative analgesia is mandatory following cesarean section (CS), as parturients need to recover quickly to breast feed and provide care for their newborns. Till date no single drug has been able to achieve this goal. Multimodal analgesia with opioids and non-steroidal anti-inflammatory drugs (NSAID) combination has shown promising results. Aims: To compare the analgesic efficacy, patient satisfaction and maternal adverse effects, between intravenous (IV) tramadol and multimodal analgesia with IV tramadol and IV ketorolac combination for post cesarean section analgesia. Methods: This is a prospective, randomized and single-blinded comparative study, conducted in 60 parturients who underwent Lower Segment Cesarian Section. They were divided into two groups: Group 1 (IV Tramadol 50 mg given 8 hourly) and Group 2 (IV Tramadol 50 mg + IV Ketorolac 30 mg given 8 hourly). IV Promethazine was given with each dose of tramadol in both groups. Results: The (Visual analogue scale) VAS scores were significantly low in IV tramadol + IV ketrolac group than with IV tramadol alone group at 2 hours and 12 hours with p value of 0.003 and 0.08 respectively. Rescue analgesia was significantly reduced in group 2 (p value 0.005). Patient satisfaction was good in group 2 and fair in group 1(p value 0.002). No maternal side effects were found. Conclusion: IV tramadol and IV ketorolac combination used for post cesarean section analgesia significantly decreases post-operative pain, need of rescue analgesia and significantly increases patient satisfaction in comparison to IV tramadol alone.